Connection and Resilience: Constructing a Measurement Tool for Teacher-Student Relationship and Resilience in the Era of Educational Disruption - Annisa Firdausy Iftitahur Rahma; Fitrania Maghfiroh (International Conference on Psychology and Education (ICPE), 2025)
This study aims to develop and validate measurement instruments for assessing teacher–student relationships and student resilience in the Indonesian educational context. The teacher–student relationship scale covers seven dimensions such as proximity seeking, emotional support, and open communication. Meanwhile, the resilience scale comprises eight dimensions including emotional, cognitive, relational, physical, motivational, spiritual, and adaptive aspects. Data were collected through two try outs using Likert scale questionnaires distributed via both paper based and Google Form to middle and high school students. Validity was tested using Pearson correlation, and reliability was confirmed through Cronbach’s Alpha. The results show high validity and reliability for both scales, with a positive correlation (r = 0.489, p < 0.05) indicating that better teacher–student relationships are associated with higher student resilience. This study contributes practical measurement tools for educational interventions to strengthen psychosocial student development in Indonesia.